Teknologi dan Kreativitas dalam Wirausaha Bagi Siswa Madrasah Aliyah (MA) Ma’arif Kotagajah Lampung Tengah - Widiyanti, Ade; Russel, Edwin; Sawitri, Riza; Mega Sapitri, Nonik; Andrade Paskalia M, Felicia (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The rapid development of information technology has brought significant changes in various fields, including the business world. This provides students with the opportunity to engage in the digital-based business world. Many students of Madrasah Aliyah (MA) Ma'arif Kotagajah, Lampung Tengah are interested in entrepreneurship. However, it is still hindered by limitations in utilizing technology and creativity to develop businesses and ventures. Therefore, this community service activity is conducted in the form of training aimed at improving students' understanding and skills. This entrepreneurship training emphasizes the use of digital technology and student creativity in entrepreneurship. The methods used include lectures, discussions, and hands-on practice related to digital marketing, digital financial management, and the development of innovative business ideas. This training is expected to equip students with practical and adaptive skills, and be prepared to compete in the modern business world.